2009
DOI: 10.1149/1.3129676
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties and Performance of Polymer Electrolyte Membranes for the Hybrid Sulfur Electrolyzer

Abstract: The water transport and SO 2 crossover in the hybrid sulfur cycle electrolyzer were quantified for a poly͑phenylene͒-based proton exchange membrane and compared to the performance of industry-standard Nafion membranes. While Nafion exhibits good performance, there exists the possibility of a significant SO 2 crossover, which can modify the electrode composition, consume current that should be used for hydrogen production, introduce SO 2 to the hydrogen stream, and result in a loss of sulfur from the system. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 16 publications
0
33
1
Order By: Relevance
“…[8][9][10][11][12] For example, Westinghouse was only able to get the cell voltage down to 1.0 V at 400 mA/cm 2 , where we achieved 500 mA/cm 2 at 0.71 V and 1.2 A/cm 2 at 1.0 V using Nafion 212 (N212). However, to achieve overall process efficiency, concentrated sulfuric acid as well as low cell voltage at high current densities are * Electrochemical Society Member.…”
Section: -6mentioning
confidence: 94%
See 1 more Smart Citation
“…[8][9][10][11][12] For example, Westinghouse was only able to get the cell voltage down to 1.0 V at 400 mA/cm 2 , where we achieved 500 mA/cm 2 at 0.71 V and 1.2 A/cm 2 at 1.0 V using Nafion 212 (N212). However, to achieve overall process efficiency, concentrated sulfuric acid as well as low cell voltage at high current densities are * Electrochemical Society Member.…”
Section: -6mentioning
confidence: 94%
“…The resulting reactions at the anode and cathode, respectively, are: 2H + + 2e − → H 2 U 0 H2 = 0 V vs. SHE [3] Thus, the overall reaction in the electrolyzer is represented as: SO 2 + 2H 2 O → H 2 SO 4 + H 2 [4] Considerable progress was made in the last decade in lowering the operating voltage and increasing the current density of the SDE by moving from a microporous rubber diaphragm separator used by Westinghouse 7 to a perfluorinated sulfonic acid membrane (e.g., DuPont's Nafion). [8][9][10][11][12] For example, Westinghouse was only able to get the cell voltage down to 1.0 V at 400 mA/cm 2 , where we achieved 500 mA/cm 2 at 0.71 V and 1.2 A/cm 2 at 1.0 V using Nafion 212 (N212). However, to achieve overall process efficiency, concentrated sulfuric acid as well as low cell voltage at high current densities are necessary.…”
mentioning
confidence: 94%
“…11,13,15,16 We showed that water transport affected the electrolyzer performance ͑i.e., cell voltage͒ by controlling the sulfuric acid concentration at the anode. We in turn developed a model to predict water flux through the membrane as a function of membrane thickness, temperature, current density, and pressure differential.…”
Section: ͓1͔mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In this thermochemical cycle, sulfuric acid is decomposed at high temperature ͑ϳ850°C͒ to SO 2 and water, and the SO 2 is converted back to sulfuric acid in a proton exchange membrane ͑PEM͒ electrolyzer. Hence, the sulfur compounds are internally recycled, such that the overall process decomposes water into hydrogen and oxygen.…”
mentioning
confidence: 99%
See 1 more Smart Citation